Commentary: Testing the general theory of crime - Hirschi, Travis (Journal of research in crime and delinquency, 1993)
This article focuses on the testing of the general theory of crime. The source of any theory is an idea, an idea the theory itself attempts to articulate or express. As a result, tests of theory are tests of the articulation of an idea and, if done properly, of the value of the idea itself. The idea that serves as the basis for "A General Theory of Crime" is the idea of control, an idea with deep roots in the thinking of ordinary people, an idea that has been used to make sense of a variety of observations in many fields of study. One issue that transcends is worthy of discussion in the context they provide is the measurement of self-control. The advantage of behavioral measures is that they counter the tendency to translate the control concept at the core of our theory into a personality concept or an enduring criminal predisposition. There may be in the theory, an enduring predisposition to consider the long-term consequences of one's acts, but there is no personality trait predisposing people toward crime. That people are not specifically predisposed to crime is the fundamental assumption of control theories, and the central reason one will continue to argue that the theory cannot be integrated with theories taking the opposite point of view